2017
DOI: 10.18632/oncotarget.14901
|View full text |Cite
|
Sign up to set email alerts
|

The DPC4/SMAD4 genetic status determines recurrence patterns and treatment outcomes in resected pancreatic ductal adenocarcinoma: A prospective cohort study

Abstract: ObjectivesThe objective of this study was to investigate the role of genetic status of DPC4 in recurrence patterns of resected pancreatic ductal adenocarcinoma (PDAC).MethodsBetween April 2004 and December 2011, data on patients undergoing surgical resection for PDAC were reviewed. Genetic status of DPC4 was determined and correlated to recurrence patterns and clinical outcomes.ResultsAnalysis of 641 patients revealed that genetic status of DPC4 was associated with overall survival and was highly correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 28 publications
2
53
1
Order By: Relevance
“…Loss of DPC4 expression is associated with distant metastasis, epithelial to mesenchymal transition, and treatment failure to local recurrence [5153]. In the present study, all 6 AMCPAC cell lines showed homogeneously intact DPC4 expression.…”
Section: Discussionsupporting
confidence: 59%
“…Loss of DPC4 expression is associated with distant metastasis, epithelial to mesenchymal transition, and treatment failure to local recurrence [5153]. In the present study, all 6 AMCPAC cell lines showed homogeneously intact DPC4 expression.…”
Section: Discussionsupporting
confidence: 59%
“…After removal of 690 duplicates, a further 2588 articles were excluded after title and abstract screening because they did not meet the prespecified inclusion criteria. The full texts of the remaining 468 studies were evaluated in more detail, and 89 studies were found to meet the eligibility criteria for this systematic review. Among them, 22 studies containing information on clinical factors relevant to recurrence sites were selected for the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The Cochrane Collaboration tool for assessing risk of bias showed that one study had no domain with a high risk of bias and three studies had one of seven domains with a high risk of bias ( Table S3 , supporting information). The overall risk of bias in non‐randomized studies, according to ROBINS‐I, was moderate in 48 studies and serious in 37 studies ( Table S4 , supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…For example, biomarkers such as Dpc4/Smad4 and Runx3 have been studied to predict the behavior of the tumor. The expression of Dpc4/Smad4 was investigated in a prospective study and correlated with recurrence pattern and treatment outcome of post‐pancreatectomy patients . Patients with gene loss of Dpc4/Smad4 were more likely to have metastatic recurrence and those with gene expression were more likely to recur locoregionally.…”
Section: Discussionmentioning
confidence: 99%